SEMIOTIC ANALYSIS: VERBAL SIGN AND NON-VERBAL SIGN FOUND AT ANIVA JUNCTION MIX-USED BUILDING - Nur Arofah; Glory Senia Maranatha Sambulare; Raudya Maghfira Muliasani (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to analyze verbal signs and non-verbal signs in the logo in the mixed-use building Aniva Junction. The object of this research is the logo in the mixed-use building Aniva Junction, Gading Serpong. The theory of Triangle meaning Pierce (2007) is used to analyze the data. This study uses qualitative descriptive methods based on Creswell & Creswell (2018). The data in this study were collected through several steps, including by visiting the mixed-use building Aniva Junction directly, then the logo was photographed and classified into the verbal sign and non-verbal sign categories. This study highlights the identification and interpretation of the meaning of the semiotic element of each logo. This study found 30 logos with verbal and non-verbal signs. Verbal signs found on logos such as words, phrases, or sentences. On the other hand, the non-verbal sign found such as color, icons, and symbols. Based on knowledge of the verbal sign and non-verbal sign, an interpretation of the meaning of a logo can be obtained.